PENGARUH RASIO KEUANGAN TERHADAP RETURN SAHAM PERUSAHAAN MANUFAKTUR YANG GO PUBLIC DI BURSA EFEK INDONESIA - Diky Wahyu Saputra; Moh. Amin; Junaidi Junaidi (Universitas Islam Malang, 2019)
ABSTRACTReturn is income expressed as a percentage of the initial investment capital. Investment income in this stock is the profit gained from buying and selling shares, where if profit is called capital gain and if the loss is called capital loss. This study aims to assist investors in making decisions as well as investing in the capital market by analyzing the effect of financial ratios on stock returns of manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the 2015-2018 period, both partially and simultaneously. Financial ratios or variables used are: current ratio (CR), debt to equity ratio (DER), return on assets (ROA), return on equity (ROE) and earnings per share (EPS). The population in this study are manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the 2015-2018 period. The research sample was 132 manufacturing companies obtained by purposive sampling technique. The data collection technique used is documentation. The method of data analysis is multiple linear regression. Hypothesis test results show that Debt Equity Ratio and Return on Equity significantly influence Stock Return, while Current Ratoi (CR), Return On Assets (ROA) and Earning per Share (EPS) do not significantly influence Stock Return. Investors should review the financial statements issued by the company and use financial ratios, especially the Debt Equity Ratio (DER) and Return on Equity (ROE) as a reference in investing. Keywords: Current Ratio, Debt Equity Ratio, Total Asset Turnover, Return on Equity and Earningper Share, Stock Price